2015
DOI: 10.1002/jhbp.299
|View full text |Cite
|
Sign up to set email alerts
|

Pancreaticoduodenectomy with venous reconstruction using cold‐stored vein allografts: long‐term results of a single center experience

Abstract: Our experience with cold-stored vein allografts suggests that this technique is a useful option for treating major vascular resections during pancreaticoduodenectomy with good results on follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 31 publications
0
10
0
2
Order By: Relevance
“…Various MPV reconstruction techniques have been described, including the use of synthetic PTFE grafts [9], bovine pericardium, allografts [5,10], autografts [7,11,12], as well as different segmental or tangential resections with primary end-to-end anastomosis or venorrhaphy [13,14], resulting in an overall patency rate between 70 and 90% [9][10][11][12][13][14]. Each technique has its own advantages and disadvantages, so far the optimal reconstruction strategy is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Various MPV reconstruction techniques have been described, including the use of synthetic PTFE grafts [9], bovine pericardium, allografts [5,10], autografts [7,11,12], as well as different segmental or tangential resections with primary end-to-end anastomosis or venorrhaphy [13,14], resulting in an overall patency rate between 70 and 90% [9][10][11][12][13][14]. Each technique has its own advantages and disadvantages, so far the optimal reconstruction strategy is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…There are very few studies reporting allograft vein graft for PV-SMV reconstruction. Roberto et al reported that allograft vein graft for PV-SMV reconstruction did not require either ABO matching or immunosuppressive therapy [ 26 ]. Manju D. Chandrasegaram et al reported that there is high heterogeneity in the use of anticoagulation policy, and the acceptable perioperative outcomes were achieved with an anticoagulation policy or no anticoagulation policy after venous resection [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Various vascular reconstructions using primary venous closure, end-to-end anastomosis, using autologous, allogenous or prosthesis graft were described in the worldwide literature. The overall patency rate of the above-mentioned reconstructions is between 70 and 90% [ 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. Each technique has its own advantages and disadvantages.…”
Section: Venous Resectionsmentioning
confidence: 99%